MICHAELIAN, Kourken. Mental Time Travel: Episodic Memory and Our Knowledge of the Personal Past. Cambridge, MA: The MIT Press, 2016. - Richter, Bruna Natália (Intuitio, 2020)
Resenha: MICHAELIAN, Kourken. Mental Time Travel: Episodic Memory and Our Knowledge of the Personal Past. Cambridge, MA: The MIT Press, 2016